PENGARUH PENDAPATAN MUSYARAKAH, MUDHARABAH, DAN MURABAHAH TERHADAP LABA BERSIH PT. BANK MUAMALAT INDONESIA, TBK. - Govi Maulana (2022)
One parameter to measure a bank's success is net income. The more one of the parameters to measure a bank's success is the net profit. The more the bank's revenue grows, the more it shows strong performance. This research aims to determine the impact of revenue from musyarakah, mudharabah and murabahah on the net profit of PT. Bank Muamalat Indonesia, Tbk with a period of 2014 to 2021. The approach used in this study is a quantitative approach based on secondary data with the sample used is the PT. Bank Muamalat Indonesia, Tbk Report from 2014 to 2021. The data analysis method used is regression linier berganda. The results showed that musyarakah's income did not have a positive impact, mudharabah's income had a positive impact, while Murabahah's income have a negative impact on net income. For the Islamic banking industry, this research can determine factors that may affect net profit and measure the performance of Islamic banks and other stakeholders.